Relevansi Pemikiran Filosofis Ki Hadjar Dewantara Terhadap Sistem Pendidikan Hindu - Gede Agus Siswadi (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
This article seeks to examine the thoughts of Ki Hadjar Dewantara who is the father of national education. With the concept of education through the